Effect of Duration of Active or Passive Recovery on Performance and Muscle Oxygenation during Intermittent Sprint Cycling Exercise - Ohya, T.; Aramaki, Y.; Kitagawa, K. (International Journal of Sports Medicine, 2013)
We compared the effect of recovery condition and durations on performance and muscle oxygenation during short-duration intermittent sprint exercise. 8 subjects performed a graded test and ten 5-s maximal sprints with 25-, 50-, and 100-s passive recovery (PR) or active recovery (AR) on a cycle ergometer. Peak power and percent decrease in power were determined. Oxygen uptake and blood lactate were measured during the sprint exercise. Oxyhemoglobin (O2Hb) and deoxyhemoglobin were measured using near-infrared spectroscopy. Peak power values were higher for PR than AR for the 25-s (2–9 sprints) and 50-s (2–6, 9, or 10 sprints) but not for the 100-s durations. Percentage decrease in peak power was lower for PR than AR in the 25-s (8.5±2.5 vs. 11.5±3.6%, P=0.008, ES=0.66) and 50-s (2.7±1.4 vs. 6.2±3.5%, P=0.007, ES=0.67) but not 100-s durations (2.1±1.3 vs. 3.1±2.6%, P>0.05). O2Hb variations were significantly higher for PR than AR for the 25-s and 50-s durations. AR was associated with reduced sprint performance and lower muscular reoxygenation. Performance was not affected over longer recovery durations regardless of recovery condition.
Keywords: near-infrared spectroscopy; repeated-sprint; field-based team sports